Agroindustrial waste application for drugs biosorption - da Costa, Matheus Londero; Resmini, João Pedro Martins; de Vasconcellos, Noeli Júlia Schüssler; da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Currently, one of the main focuses globally is the stability of the environment for future generations. For this to be possible, it is necessary to preserve natural resources, such as water, as it is essential for the continuity of life on the planet. However, due to the massive increase in residual water and the improper consumption of medications, which are generally not fully metabolized, being excreted inappropriately, becoming an environmental liability. In this context, several treatment techniques have been used to promote the correct disposition for this wastewater, highlighting the adsorption process due to its ease, low cost, and the possibility of using alternative materials (biosorbents). Thus, the present work aims to present a bibliographic review of a qualitative and exploratory character on the application of agro-industrial residues, as alternative materials, for the removal of medicines, through a study of adsorption equilibrium, using the Langmuir, Freundlich, Temkin and Sips isotherms and adsorption kinetics, using the Pseudo-First-Order, Pseudo-Second-Order and Elovich models. Therefore, research demonstrated positive results in the removal of organic pollutants such as the industrial use of cork and peach kernel for the removal of paracetamol, where a Qmáx of 200 and 113 mg g-1 was obtained for Langmuir , n of 3.1 and 2.4 for Freundlich agreeing with the same, and having an optimal Pseudo-Second-Order kinetics of R2 of 0.999 for both, therefore, with this article it was possible to verify the use of several biosorbent in the removal of the mentioned drugs previously.